Implementasi Website Informasi Desa Badas Kecamatan Sumobito sebagai Upaya Digitalisasi Layanan Publik dan Transparansi Informasi Desa - Arivatu Ni'mati Rahmatika; Bekti Widyaningsih; Adinda Fadia Salsabila; A'tini Hidayatika; Afrizal Armansyah; Hoffy Zahwa Hanani (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The community service program in Badas Village, Sumobito District, aimed to enhance information transparency and the effectiveness of public services through the implementation of an official village website. The method used was Participatory Action Research (PAR) with stages including observation, design, development, training, socialization, and handover. The results showed that the village website was successfully developed and utilized as a medium for information dissemination, local potential promotion, and digital-based administrative services. Village officials were able to upload and manage content independently after receiving training, while the community benefited from easier access to information without visiting the village office. In addition, a website management manual was provided as a sustainability instrument. The impacts included improved transparency, promotion of local economic potential, and enhanced human resource capacity among village officials. Thus, this program contributed to the realization of modern, accountable, and competitive village governance.